Advanced Technical Pearls for Successful Supermicrosurgical Lymphaticovenular Anastomosis. Issue 2 (March 2021) - Chen, Wei F.; Tuncer, Fatma Betul; Zeng, Weifeng
Abstract : Abstract: Lymphaticovenular anastomosis (LVA) is now accepted as one of the mainstays of surgical treatment of lymphedema. The unique advantages of LVA that set it apart from other procedures such as vascularized lymph node transfer are its safety and its minimally invasive nature. To date, there has been no report of worsening of disease as a result of LVA, even when performed unsuccessfully. Despite these notable advantages, the procedure is much less frequently performed compared with vascularized lymph node transfer because of inconsistent procedural outcome. In our experience, LVA is highly effective when performed with proper patient selection and meticulous technical execution. In this article, we share the senior author's LVA "tips and tricks" to help readers achieve greater success when performing this extraordinary supermicrosurgical procedure. Abstract : Supplemental digital content is available in the text.